Mapping cones of positive maps - Størmer, Erling (MATHEMATICA SCANDINAVICA, 2011)
We study mapping cones of positive maps of B(H) into itself, i.e., cones which are closed under composition with completely positive maps. As applications we obtain characterizations of linear functionals with strong positivity properties with respect to so-called symmetric mapping cones, with special emphasis on separable and PPT states.